2011
DOI: 10.5194/bg-8-113-2011
|View full text |Cite
|
Sign up to set email alerts
|

Deep plant-derived carbon storage in Amazonian podzols

Abstract: Equatorial podzols are soils characterized by thick sandy horizons overlying more clayey horizons. Organic matter produced in the topsoil is transferred in depth through the sandy horizons and accumulate at the transition, at a depth varying from 1 to more than 3 m, forming deep horizons rich in organic matter (Bh horizons). Although they cover great surfaces in the equatorial zone, these soils are still poorly known. Studying podzols from Amazonia, we found out that the deep Bh horizons in poorly drained podz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
1
32
1
1
Order By: Relevance
“…Sierra et al (2013) used a compartment model that was constrained by 14 C dating to estimate the carbon fluxes in a Colombian shallow podzol (Bh upper limit at 0.9 m). They showed that the C fluxes from topsoil horizons to the Bh horizon were smaller (2.1 gC m −2 year −1 ) than the fluxes estimated in Montes et al (2011). However, they did not account for the age and genesis time of the Bh horizon.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Sierra et al (2013) used a compartment model that was constrained by 14 C dating to estimate the carbon fluxes in a Colombian shallow podzol (Bh upper limit at 0.9 m). They showed that the C fluxes from topsoil horizons to the Bh horizon were smaller (2.1 gC m −2 year −1 ) than the fluxes estimated in Montes et al (2011). However, they did not account for the age and genesis time of the Bh horizon.…”
Section: Introductionmentioning
confidence: 91%
“…In wet tropical areas podzols can be very deep, with E horizons thicker than 10 m and Bh horizons thicker than 4 m (Chauvel et al, 1987;Dubroeucq and Volkoff, 1998;Montes et al, 2011). This means that they can store huge quantities of organic matter: Montes et al (2011) estimated the C stocks in Amazonian podzols to be around 13.6 Pg C.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations